Phase II Study of Low‐Dose Afatinib Maintenance Treatment Among Patients with EGFR‐Mutated Non‐Small Cell Lung Cancer: North Japan Lung Cancer Study Group Trial 1601 (NJLCG1601). (7th July 2020) - Nakamura, Atsushi; Tanaka, Hisashi; Saito, Ryota; Suzuki, Aya; Harada, Toshiyuki; Inoue, Sumito; Yamada, Toru; Nakagawa, Taku; Jingu, Daisuke; Sugawara, Shunichi
Abstract: Lessons Learned : Low‐dose afatinib maintenance treatment among patients with EGFR ‐mutated NSCLC achieved long‐time to treatment failure with fewer treatment‐related AEs without detracting from the therapeutic efficacy. This modified regimen represents a practical usage that balances effectiveness and safety. Background: Although afatinib is an effective therapy for patients with EGFR ‐mutated non‐small cell lung cancer (NSCLC), drug‐related adverse events (AEs) have often necessitated dose reductions. In a post hoc analysis of the LUX‐Lung 3 and 6 trials, there was no difference in median progression‐free survival (PFS) between patients who had the dose of afatinib reduced and those who did not. We thus evaluated the efficacy and tolerability of low‐dose afatinib maintenance treatment among patients with NSCLC harboring EGFR mutations who had not been previously treated. Methods: Eligible patients received afatinib 40 mg orally once daily. When prescribed grade ≥ 2 AEs, rash of grade ≥ 3, or unacceptable toxicity occurred, the afatinib dose was reduced from 40 to 30 mg and if needed from 30 to 20 mg. The primary endpoint was the 1‐year PFS rate. Secondary endpoints were PFS, overall response rate (ORR), and toxicity. Results: Among 30 patients, 93% had adenocarcinoma, 53% had exon 19 deletion, 37% had L858R, and 10% had minor mutations. The 1‐year PFS rate was 50% (95% confidence interval [CI], 31.3–66.1) and the median PFS was 11.8 months (95% CI, 7.1–21.4). The incidence rate of grade ≥ 3 toxicities was 57%, including elevated aspartate aminotransferase/alanine aminotransferase level (13%), diarrhea (10%), and paronychia (10%). Conclusion: Low‐dose afatinib maintenance treatment reduced treatment‐related AEs without detracting from the therapeutic efficacy.